1994
DOI: 10.1002/j.1460-2075.1994.tb06263.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and inhibition of a Plasmodium falciparum aspartic hemoglobinase.

Abstract: Intraerythrocytic malaria parasites rapidly degrade virtually all of the host cell hemoglobin. We have cloned the gene for an aspartic hemoglobinase that initiates the hemoglobin degradation pathway in Plasmodium falciparum. It encodes a protein with 35% homology to human renin and cathepsin D, but has an unusually long pro‐piece that includes a putative membrane spanning anchor. Immunolocalization studies place the enzyme in the digestive vacuole and throughout the hemoglobin ingestion pathway, suggesting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
207
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(216 citation statements)
references
References 52 publications
7
207
1
1
Order By: Relevance
“…13. The V-ATPase responsible for acidifying the FV is present in the parasite surface membranes (Marchesini et al, 2005) and FV-resident proteases were shown to localize to the cytostome (Francis et al, 1994;Klemba et al, 2004). FV components are, therefore, present in membranes contiguous with the cytostome.…”
Section: A New Model For Hemoglobin Transportmentioning
confidence: 99%
“…13. The V-ATPase responsible for acidifying the FV is present in the parasite surface membranes (Marchesini et al, 2005) and FV-resident proteases were shown to localize to the cytostome (Francis et al, 1994;Klemba et al, 2004). FV components are, therefore, present in membranes contiguous with the cytostome.…”
Section: A New Model For Hemoglobin Transportmentioning
confidence: 99%
“…Hemoglobinolysis was also monitored at 410 nm using a spectrophotometer and reversed phase (RP)-HPLC. 1 …”
Section: Determination Of Subsite Preferences Using Positional Scannimentioning
confidence: 99%
“…In P. falciparum several proteases have been identified in the food vacuole that are involved in hemoglobin degradation, including a family of aspartic proteases known as the plasmepsins (2,3). The four plasmepsins found in the food vacuole of P. falciparum are PfPM1, PfPM2, PfPM4, and the histoaspartic protease (HAP) (3,4). It is now believed that the enzymes from P. vivax (PvPM4), P. ovale (PoPM4), and P. malariae (PmPM4) are orthologs of PfPM4 (5 (3,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The four plasmepsins found in the food vacuole of P. falciparum are PfPM1, PfPM2, PfPM4, and the histoaspartic protease (HAP) (3,4). It is now believed that the enzymes from P. vivax (PvPM4), P. ovale (PoPM4), and P. malariae (PmPM4) are orthologs of PfPM4 (5 (3,(6)(7)(8)(9). Therefore, the PfPM4 orthologs would be excellent targets for a single drug therapy directed at all four plasmodium species (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation